An American girl in London : 120 nourishing recipes for your family from a Californian expat - Hermer, Marissa (New York : Rodale, 2017)
"For Marissa Hermer, star of Bravo's hit show Ladies of London, a house just isn t ahome until pots are simmering on the stove and a roast is fragrant in the oven. And growing up in Southern California, she ate avocados picked from her grandmother s tree and freshly caught fish from Newport Beach.So when she followed the love of her life to London in 2008, Hermer wasn't quite sure what to expect. On one of their first dates, now-husband Matt took her to the popular Notting Hill location of his beloved Bumpkin restaurant, which features a traditional British seasonal menu using sustainable ingredients. Hermer was immediately inspired: She started incorporating California twists into English fare, delighting her two boys at home and eventually, Bumpkin fans all over London. An American Girl inLondon is the ultimate cookbook for anyone looking for wholesome, family-friendly fare with a healthy twist the recipes spotlight unprocessed, sustainable, and fresh ingredients. From a flavorful sourdough bread and butter pudding to a rich Beef Wellington, Hermer shows you how to amp up the flavors of home and keep you, your family, and friends feeling fit, loved, and completely nourished." -- provided by publisher.
Includes index.
Keywords: Cooking; Cooking, American; Cooking, British; Cooking; Cooking, American; Cooking, British; Cookbooks; Cookbooks